Arterial pulse waveform and PWV - Tung, Chun Ho (Nanyang Technological University, 2022)
The project involves the study of the arterial pulse waveform and pressure index for both healthy and hypertension participants from different age groups. This project aims to understand the relationship between arterial pulse waveform and health conditions for different age groups. Developing average arterial pulse waveforms for different age groups for doctors to use for diagnosing patients. With the use of pulse traxer™ PT8080 provided by HealthStats International Pte Ltd, which uses a non-invasive sensor module. The sensor module straps around the person’s wrist to measure the arterial pulse waveform. This device utilizes applanation tonometry to measure arterial pressure on the wrist. Pulse Traxer software is used to collect data. Another software used is Excel, a powerful a well-known software so anyone can increase the database of the arterial pulse waveforms collected and allow doctors to use it to diagnose patients with heart damage and blood vessels clot easily. A total of 29 participants’ data were collected for this project. Out of the 29 participants, 21 are aged 20 to 25. Due to many arterial pulse waveforms being identical, only 10 were used in the analysis. The other 8 participants are aged 59 to 65. The age gap is selected to be far apart to compare health conditions in different age groups. 168 pulses are collected from each participant however, only 30 pulses that best represent all the pulses are used in the analysis. All pulse waves are equalised to have the same height and width for comparison of pulse waveform shape between participants. PR and RNA which have negative and positive correlations respectively are the only pressure indexes found to make a linear correlation with age. SYS, DIA, MAP, MSP and MDP have a nonlinear correlation with age due to heart weakening and clots in blood vessels. SUG and SPT are not useful due to pulse waves being equalised. Pulse waveform shapes are compared by superimposing the pulse waveforms of different participants to compare the difference. The small notch during the systolic decline is a significant indicator of a person's health condition discovered in this research. All pulse is combined and averaged according to their age groups. Allowing doctors to compare pulse waveforms to analyse the patient’s health condition.